Tingkat Kinerja MHD Villa Syariah di Kota Bukittinggi - Nency Ayu Wandira; Emrizal, Emrizal; Marciella Elyanta (Yayasan Literasi Sains Indonesia, 2025)
The background of this research is the unmet customer expectations. This study aims to determine the performance level of MHD Villa Syariah in Bukittinggi City. The research used a mixed method (quantitative and qualitative) with a sample of 30 respondents. Primary data were interviews with the Manager of MHD Villa Syariah and the management of MHD Villa Syariah. Secondary data sources included documentation reports, books, scientific journals, and previous research. Data were collected through observation, interviews, and questionnaires. Phenomenological data analysis (data reduction, data presentation, conclusion drawing) and importance performance analysis were used. The results of this study indicate that the performance level of MHD Villa Syariah is good and can be optimized by further improvements in quadrant one, such as parking management, facilities for ablution (wudu) and prayer, owners, staff, and covering their genitals in accordance with less stringent Sharia principles, understanding customer needs and ensuring safety, staff consistency in providing service, and the availability of public transportation from various locations to MHD Villa Syariah.